Applied numerical methods for engineers - Akai, Terrence J. 1949- (John Wiley & Sons, 1993)
Written for engineering students, this textbook on numerical methods stresses the typical methods that engineers use in daily practice. A chapter on design introduces problems which bring relevance to the use of this tool in engineering situations